Systematic review: Use of imaging exams to help diagnose infectious tenosynovitis - Simões, Marcela Rodrigues Costa; Nery, Amanda Fagundes (Seven Editora, 2023)
Infeccious Tenosynovitis is a disease that affects tendon sheath, normal hand tendons . The origin can be hematogenous, trauma dito inoculation of pathogens ir local spread. This study aims to evaluate the use of ultrasound examination in the diagnostic approach and therapeutic follow-up in patients with tenosynovitis. This is a systematic review study, which had the PUBMED and SCIENCE DIRECT databases as a research source, selecting studies between the years 2018 and 2023. 15 articles that responded to the proposed objective and suited the criteria were analyzed. of inclusion. It was possible to verify that patients affected by infectious tenosynovitis are generally male (53.3%). They are usually over 30 years old (80.0%), and may also affect children (20.0%). Most individuals were diagnosed with pyogenic flexor tenosynovitis (53.3%). All studies used ultrasound as one of the diagnostic methods (100.0%). Among the treatments used, there was a higher prevalence of antibiotic therapy (86.6%) and surgical debridement (40.0%). According to the analysis carried out, it was possible to verify that ultrasound at the bedside is an important imaging modality, and its use should be considered in patients with suspected pyogenic tenosynovitis, due to its speed and greater sensitivity, as it makes it possible to treat the patient without surgical intervention and helps in choosing the best treatment. DOI:https://doi.org/10.56238/innovhealthknow-058